Top Brand Award Ranking Analysis Using Social Network Analysis on Coffee Shops on Twitter Social Media - herdiany, alvioneta dinda; Asih, Tri Sri Noor (Unnes Journal of Mathematics, 2025)
The coffee shop business is one of the very busy businesses. A number of coffee shop brands in Indonesia have begun to emerge. One of the fastest growing fast food coffee chains in Indonesia is Kopi Kenangan. Top Brand is conducting a poll in 2023 to determine the preferred level of consumption for local coffee. According to the findings of the Top Brand Award 2023 survey, Kenangan coffee with a value of 39.70% occupies the first position in the online and offline food and beverage category, while Janji Jiwa coffee is in second place with a value of 39.50%. Janji Jiwa Coffee is one of the fast-growing franchise companies in Indonesia. This study uses the Social Network Analysis (SNA) method to find out which coffee shop brands have higher activity by comparing network properties on Twitter social media. The source of this research data was obtained from the results of crawling data on Twitter social media with the keywords "Kopi Kenangan" and "Kopi Janji Jiwa" for 2 months from November 1, 2023 – December 30, 2023 using Python, with the results of Kenangan copies of 1605 tweets, and Janji Jiwa copies of 1653 tweets. Then text preprocessing is done using Python. Furthermore, visualization was carried out for both coffee shop brands using Python consisting of top word, wordcloud top word, top actor poster, and top mentioned account. After that, making a network pattern graph model using the Gephi application with the Yifan Hu Proportional layout. Followed by an analysis of the network property values of the two brands to be compared. The comparison of the value obtained between the two coffee shop brands, namely the Janji Jiwa coffee shop, excels in 3 network property values such as size, avg. degree, and modularity. While the Kenangan coffee shop is only superior to 1 network property value, namely avg. path length. Other network property values, namely network density and diameter of Kenangan coffee shop and Janji Jiwa coffee shop have the same value. The results of the ranking analysis get different results from brand ranking using the Top Brand Award, namely Janji Jiwa coffee shop ranked 1st and Kenangan coffee shop ranked 2nd. While in the Top Brand Award, Kenangan coffee shop ranked 1st and Janji Jiwa coffee shop ranked 2nd.